Involvement of BcYak1 in the Regulation of Vegetative Differentiation and Adaptation to Oxidative Stress of Botrytis cinerea - Yang, Qianqian; Zhang, Jianan; Hu, Jicheng; Wang, Xue; Lv, Binna; Liang, Wenxing (Frontiers in Microbiology, 2018)
Yak1, a member of the dual-specificity tyrosine phosphorylation-regulated protein kinases, plays an important role in diverse cellular processes in fungi. However, to date, the role of BcYak1 in Botrytis cinerea, the causal agent of gray mold diseases in various plant species, remains uncharacterized. Our previous study identified one lysine acetylation site (Lys252) in BcYak1, which is the first report of such a site in Yak1. In this study, the function of BcYak1 and its lysine acetylation site were investigated using gene disruption and site-directed mutagenesis. The gene deletion mutant ΔBcYak1 not only exhibits much lower pathogenicity, conidiation and sclerotium formation, but was also much more sensitive to H2O2 and the ergosterol biosynthesis inhibitor (EBI) triadimefon. The Lys252 site-directed mutagenesis mutant strain ΔBcYak1-K252Q (mimicking the acetylation of the site), however, only showed lower sclerotium formation and higher sensitivity to H2O2. These results indicate that BcYAK1 is involved in the vegetative differentiation, adaptation to oxidative stress and triadimefon, and virulence of B. cinerea.